Childfree dalam Perspektif Islam: Solusi atau Kontroversi? - Desi Rahman; Alya Syahwa Fitria; Dhea Anisa Lutfiyanti; Ilyasa Irfan M R; Shakira Mauludy Putri Fadillah; Muhamad Parhan (Pusat Studi Wanita dan Keluarga UGM, 2023)
Childfree is an agreement made by a husband and wife not to have children during their marriage. There are many reasons why someone and their partner have a view like this. The reasons are: (1) Economic Factors, (2) Mental or Psychological Factors, (3) Personal Factors and Experience, (4) Environmental Factors, (5) Medical Factors, and (6) Educational Factors. This research examines childfree from an Islamic perspective which aims to discuss the phenomenon of childfree which is being stirred up and reaping debate in society and is motivated by cases that are currently being discussed. This study uses a qualitative approach by using a literature review in collecting data. The sources used as references in this research are the Al-Qur'an, scientific journals, Hadith, and other sources. In Fiqh, childfree is a decision that is prohibited in Islam because the application of childfree is based on reasons that seem too mundane such as the economy, education, environment, and others. Whereas in Islam it has been explained that children have many advantages and blessings in this world and the afterlife. Even though no verse directly prohibits childfree, the choice for childfree-ness can be said to be a choice that cannot be justified or blamed because it is an individual right or a right that has been decided with the family which cannot be intervened by other people's views.